Integrated plant nutrient management in sub-Saharan Africa: from concept to practice - Vanlauwe, B.; Diels, J.; Diels, J.; Merckx, R.; Merckx, R.; Sanginga, N.; Sanginga, N.; Vanlauwe, B. (Wallingford :CABI Publishing, 2001)
This book contains 23 peer-reviewed papers presented during the 'International Symposium on Balanced Nutrient Management Systems' which was held between 9 and 12 October 2000 in Cotonou, Republic of Benin. This book is presented in seven sections (i) general introduction; (ii) variability on physical and socioeconomic factors and its consequences for selection of representative areas for integrated nutrient management (INM) research; (iii) soil processes determining nutrient dynamics, particularly N and P; (iv) interactions between organic and mineral nutrient sources; (v) improved utilization of rock phosphate; (vi) decision support systems to improve resource use at farm level: on-farm testing of improved technologies; and (vii) recommendations. The currently accepted INM approach advocates the use of organic resources and mineral fertilizer inputs to redress nutrient depletion and sustain crop production. It also ensures that development of nutrient management strategies is problem-driven and involves farmers that are the end-users of such technologies.
Keywords: FF061 - Plant Nutrition; FF100 - Plant Production; JJ200 - Soil Chemistry and Mineralogy; JJ600 - Soil Fertility; JJ700 - Fertilizers and other Amendments; PP600 - Pollution and Degradation; Africa South of Sahara